MORPHOLOGICAL CHANGES IN THE PANCREAS OF OFFSPRING BORN FROM MOTHERS WITH EXPERIMENTAL DIABETES - Sabirov U., Adilbekova D.B., Akhrorov A.A., Toshpulatov S.S. (Central Asian Journal of Medicine, 2025)
Diabetes mellitus (DM) in the mother is a serious metabolic disorder that profoundly affects fetal development, in particular, the morphogenesis and functional maturation of the pancreas. This review summarizes the experimental data of studies investigating the morphological and functional state of the pancreas in the offspring of diabetic rat mothers. Using alloxan citrate buffered diabetic rat models, the researchers demonstrated that maternal hyperglycemia impairs pancreatic development, resulting in structural abnormalities such as reduced beta-cell mass, disorganized islet architecture, and impaired endocrine function in the offspring. Histopathological analyses reveal marked changes including reduced islet density, fibrosis, and irregular vascularization, which may contribute to long-term metabolic dysfunction, suggesting impaired adaptive mechanisms in glucose homeostasis. Mechanistically, these effects are attributed to intrauterine oxidative stress, epigenetic modifications, and altered expression of critical developmental genes. The results highlight the importance of glycemic control during pregnancy to mitigate the adverse effects of programming on pancreatic health in the offspring. Furthermore, this review highlights gaps in current research, such as the long-term consequences of these changes in adulthood and potential therapeutic interventions. Understanding these mechanisms may inform strategies to prevent metabolic disorders in individuals exposed to a diabetic intrauterine environment.